In vitro anti-Leishmania activity of triclabendazole and its synergic effect with amphotericin B - Borges, Beatriz Santana; Bueno, Gislayne de Paula; Tomiotto-Pellissier, Fernanda; Figueiredo, Fabiano Borges; Soares Medeiros, Lia Carolina (Frontiers in Cellular and Infection Microbiology, 2023)
Leishmaniasis is a neglected tropical disease, with approximately 1 million new cases and 30,000 deaths reported every year worldwide. Given the lack of adequate medication for treating leishmaniasis, drug repositioning is essential to save time and money when searching for new therapeutic approaches. This is particularly important given leishmania-sis’s status as a neglected disease. Available treatments are still far from being fully effec-tive for treating the different clinical forms of the disease. They are also administered par-enterally, making it challenging to ensure complete treatment, and they are extremely toxic, in some cases, causing death. Triclabendazole (TCBZ) is a benzimidazole used to treat fasciolosis in adults and children. It presents a lower toxicity profile than amphotericin B (AmpB) and is administered orally, making it an attractive candidate for treating other par-asitoses. The mechanism of action for TCBZ is not yet well understood, although potential microtubules, polyamines, or ergosterol biosynthesis in the parasite could act as a pharma-cological target. TCBZ has already shown antiproliferative activity against T. cruzi, T. brucei, and L. infantum. However, further investigations are still necessary to elucidate the mechanisms of action of TCBZ. This study therefore aimed to evaluate the in vitro effects of TCBZ on the L. amazonensis strain of Leishmania. The selectivity index (SI = CC50/IC50) of TCBZ was comparable with AmpB in promastigotes and amastigotes. Evaluation of the cell cycle showed an increase of up to 13% of cells concentrated in S and G2, and morphological analysis with scanning electron microscopy showed a high frequency of dividing cells. The ultrastructural analysis demonstrated large cytoplasmic lipid accumulation, which could suggest alterations in lipid metabolism. Combined admin-istration of TCBZ and AmpB demonstrated a synergistic effect in vitro against intracellu-lar amastigote forms with FICs of 0.25. Considering that TCBZ has the advantage of being inexpensive and administrated orally, these results suggest that TCBZ, combined with AmpB, is a promising candidate for treating leishmaniasis with reduced toxicity.